2012
DOI: 10.1128/aem.01018-12
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analyses of Drinking Water Receiving Different Disinfection Treatments

Abstract: ABSTRACTA metagenome-based approach was used to assess the taxonomic affiliation and function potential of microbial populations in free-chlorine-treated (CHL) and monochloramine-treated (CHM) drinking water (DW). In all, 362,640 (averaging 544 bp) and 155,593 (averaging 554 bp) pyrosequencing reads were analyzed for the CHL and CHM samples, respectively. Most annotated proteins were found to be of bacterial origin, although eukaryotic, archaeal, and viral proteins were also id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
132
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 55 publications
19
132
2
Order By: Relevance
“…These findings were consistent with those from previous studies showing that mycobacterial populations are frequently abundant in DWDS because of their high resistance to chlorine, monochloramine, and other disinfectant compounds in water systems (1,22,77). The high abundance of mycobacterial populations in the shower hose biofilms contrasted with their low abundance or absence in microbial communities on the surface of the ICU in a hospital in Spain, which consisted predominantly of Staphylococcaceae and Enterobacteriaceae (see Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings were consistent with those from previous studies showing that mycobacterial populations are frequently abundant in DWDS because of their high resistance to chlorine, monochloramine, and other disinfectant compounds in water systems (1,22,77). The high abundance of mycobacterial populations in the shower hose biofilms contrasted with their low abundance or absence in microbial communities on the surface of the ICU in a hospital in Spain, which consisted predominantly of Staphylococcaceae and Enterobacteriaceae (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Some NTM species have been linked to hypersensitivity pneumonitis, cervical lymphadenitis, allergies, and respiratory problems, mainly in immunocompromised individuals (18,19). NTM growing in biofilms have been identified in drinking water systems, on polyvinyl chloride (PVC) surfaces, and on showerheads from hospitals, houses, and workplaces (20)(21)(22). Their frequent occurrence in such habitats may be explained by their ability to survive stressors commonly found in distribution systems, such as oligotrophic conditions, chlorination, and hot temperatures (23,24).…”
mentioning
confidence: 99%
“…For sequencing of the genus Mycobacterium, hsp65, dnaJ, or rpoB genes have been used (Mendum et al 2000;Angenent et al 2005;Feazel et al 2009). Next generation sequencing based on pyrosequencing techniques has also been used for the identification of bacterial and mycobacterial diversity Gomez-Alvarez et al 2012). The discovery of insertion sequences which are specific for certain mycobacterial species or complexes has been crucial for their direct detection using PCR or real time PCR.…”
Section: Identification Of Mycobacteriamentioning
confidence: 99%
“…While quantifying/assigning relative proportions of the component organisms and/or gene sequences is popular by metagenomic studies [4,7,[18][19][20], what has not been addressed are estimations of technical confidence, or uncertainty, with the importance of experimental design to capture repeatability being highlighted in very prominent journals [21]. To confound this, there are few commercially available materials for metagenomic analysis and actual gDNA reference materials are limited to individual microbes [22].…”
Section: Considerations For Developing Control Materials For Metagenomentioning
confidence: 99%
“…The term environment in this context refers not only to the classic outdoor terrestrial [1] and aquatic [2,3] domains, but also environments found within other organisms, like the gut [4,5] and associated matrices like probiotic supplements [6] or linked to other man-made scenarios like water purification [7] or during fermentation [8]. The field of metagenome analysis (metagenomics) has grown rapidly as the last 10 years have seen the development and establishment of next generation (also termed massively parallel) sequencing (NGS), a technique that has the potential to read over a billion sequences in a single run.…”
Section: Introductionmentioning
confidence: 99%